Development of vaccines for Chagas disease (CRUZIVAX): stakeholders' preferences and potential impacts on healthcare - Francesco Ramponi; Céline Aerts; Paula Sartor; María Jesús Pinazo; Héctor Freilij; Carlos A. Guzmán; Emilio Malchiodi; Elisa Sicuri (Elsevier, 2023)
A vaccine for Chagas disease does not currently exist. This study aims to inform the development of two vaccines for the prevention and treatment of Trypanosoma cruzi infection, and guide their pre-clinical phase up to clinical phase I. The three main objectives are: 1) to explore patients' and policy makers' preferences on the candidate vaccines in Argentina and Spain; 2) to investigate health-related quality of life of patients affected by Chagas disease; and 3) to assess the potential health provider savings associated with the vaccines, in terms of resource use and health care costs. Discrete choice experiments will be employed to estimate and characterize the theoretical demand for the vaccines and investigate patients' and policy makers' preferences. Health-related quality of life will be assessed using the EQ-5D-3L questionnaire. Resources use and costs associated with Chagas disease will be investigated using information from the databases of the Hospital Clínic of Barcelona. Resumen: No existen vacunas para la enfermedad de Chagas. Este trabajo pretende informar la fase preclínica de dos vacunas para la prevención y el tratamiento de la infección por Trypanosoma cruzi. Los objetivos principales son tres: 1) investigar las preferencias de los pacientes y de los responsables de políticas sanitarias en Argentina y España; 2) investigar la calidad de vida relacionada con la salud de los pacientes afectados por la enfermedad de Chagas; y 3) estimar los ahorros potenciales asociados con las vacunas para los proveedores de salud. Se usarán experimentos de elección discreta para estimar y caracterizar la demanda teórica de las vacunas e investigar las preferencias de los pacientes y de los responsables de las políticas sanitarias. La calidad de vida relacionada con la salud se evaluará mediante el cuestionario EQ-5D-3L. Se investigarán el uso de recursos y los costes asociados a la enfermedad de Chagas utilizando bases de datos del Hospital Clínic de Barcelona.